EDUKASI PENERAPAN PROTOKOL 5M COVID-19 DI WILAYAH DESA KOTING C KABUPATEN SIKKA - Jesica Angelina Dua Meak; Serlie K. A. Littik; S.P. Manongga (LPPM Universitas Bina Bangsa, 2022)
Covid-19 is a health problem discovered and is a priority for intervention in RT 010, Koting C Village, Sikka Regency. Behavior is an integral part of the knowledge system owned by the community and how to respond to the Covid-19 pandemic through preventive measures by implementing the health protocols they embody. This service activity is carried out using intervention and evaluation methods to the community aimed at changing mindsets and behavior and increasing the level of willingness or awareness of the community so that they can adapt to new habits in the face of the Covid-19 pandemic. Based on the intervention result, 9 out of 15 household heads experienced behavioral changes in applying health protocols. With this habit, it is hoped that the community can maintain their and their family's health and avoid being affected by other adverse impacts due to the Covid-19 pandemic